Research of dynamic processes in the control system of the hydraulic drive of belt conveyors with variable cargo flows - Polishchuk, Leonid; Kharchenko, Yevhen; Piontkevych, Oleh; Koval, Oleh (Eastern-European Journal of Enterprise Technologies, 2016)
The dynamic processes in the hydraulic drive control system of the conveyor with parallel hydraulic motors were studied using a mathematical model, constructed on the basis of physical phenomena occurring during the variable load acting on the hydraulic system. The obtained results allow justifying the settings of the conveyor hydraulic drive control system, which provide continuous operation of the hydraulic drive system under short-term or long-term overloads and switching on and off the additional hydraulic motor in the given regimes depending on the moment of useful resistance on the drive conveyor drum. The analysis of theoretical graphs showed that the shut-off-and-regulating element of the control unit provides the desired mode of the system with a delay in the friction clutch engagement after switching on the additional hydraulic motor for its acceleration in the idle mode, thereby the executive body effectively overcomes the short-term and long-term overloads of the drive system. The influence of the specific volume of the additional hydraulic motor, relationships of the sealing areas of the shut-off element, plunger mass and damping coefficient of the control system, as well as the mode of the load changes on the control system transients was determined. The values of the specific volume of the additional hydraulic motor, relationships between the sealing areas of the shut-off element affect the stability of the sensor transients. To avoid a vacuum cavity in the additional hydraulic motor during the friction clutch disengagement, it is needed to install a check valve between the pressure and discharge lines. The mass change or damping of the plunger by connecting the parallel check valve and throttle provide vibration damping during the clutch disengagement. To prevent the adjustment overpressure in the sensor, it is needed to install the safety-relief valve in the hydraulic system, which limits the pressure in the pressure line. The efficiency of using a direct-acting valve with parametric control as a sensor in the control device, which allows regulating the closing pressure by the selection of the valve geometric characteristics independently of the mode of the load changes was proved. The research results can be used for hydraulic drives of the machines of various technological purposes that operate under variable loads.